The causes and consequences of venture capital stage financing - Tian, Xuan (Journal of Financial Economics, 2011)
This paper examines the causes and consequences of venture capital (VC) stage financing. Using information about the physical location of an entrepreneurial firm and the geographic distance between the VC investor and the firm, I show that VC investors located farther away from an entrepreneurial firm tend to finance the firm using a larger number of financing rounds, shorter durations between successive rounds, and investing a smaller amount in each round. However, VC investors' propensity to stage is independent of whether the firm is located in a close-knit community. I also find that VC staging positively affects the entrepreneurial firm's propensity to go public, operating performance in the initial public offering (IPO) year, and post-IPO survival rate, but only if the firm is located far away from the VC investor. However, the effect of VC staging on entrepreneurial firm's performance is independent of whether it is located in a close-knit community. The findings are robust to a variety of alternative proximity measures, instrumental variables, and econometric approaches for dealing with endogeneity problems.